A Modified Davidon-Fletcher-Powell Method for Solving Nonlinear Optimization Problems - Al-Issa, Ali Joma'a; Hassan, Basim A.; Moghrabi, Issam A R; Sulaiman, Ibrahim M. (Iraqi Journal of Science, 2024)
One of the quasi-Newton update formulae, namely the Davidon-Fletcher-Powell method, is crucial for resolving nonlinear programming optimization problems. In order to achieve a Newton-like condition that depends on the function values and gradient vectors at each iteration, we construct an alternative positive-definite Hessian approximation in this study. The essential theorems are established to study algorithm convergence. The proposed approach is then tested on well-known test problems and then compared to the standard DFP method. The numerical outcomes demonstrate the effectiveness of the newly developed method.